Computer vision and graphics : international conference, ICCVG 2020, Warsaw, Poland, September 14-16, 2020, Proceedings /: international conference, ICCVG 2020, Warsaw, Poland, September 14-16, 2020, Proceedings. ([2020]) - Unknown
No abstract available